Valuation of sewage sludge ash as a component of precast concrete - Baeza Brotons, F.; Garcás Terradillos, P.; Payá Bernabeu, J.; Galao Malo, O. (Revista ALCONPAT, 2015)
This paper proposes binary and ternary combinations of sewage sludge ash (SSA) with fly ash, marble dust and rice hull ash, as partial replacement or addition relative to Portland cement in concretes with a similar dosage to that used in the manufacture of precast blocks, with very dry consistency given its manufacturing process in plant. Several physical-mechanical tests were carried out on concrete and mortar specimens with curing ages of 28 and 90 days: density, water absorption and compressive strength. It is proved that replacing cement by SSA involves a decrease in density and compressive strength compared to the reference sample, however, the combinations of residues significantly improve the characteristics of the cementitious materials. The addition of SSA provided densities and resistances similar to the control sample and significantly reduces the water absorption. Keywords: sustainability, industrial products, mineral additions.